The Concept of Obligations Erga Omnes in International Law - المالكي, هادي نعيم; علي, علي فارس (Journal of Legal Sciences, 2021)
The International Court of Justice, as the main judicial organ of the United Nations in its ruling on the Barcelona Traction case, raised the concept of obligations Erga Omnes in international law, but this Latin term Erga Omnes has been used with different meanings and connotations. Through the extrapolation of the jurisprudence of the International Court of Justice, we note that it used the term In the context of its traditional meaning of expressing issues related to protest and legal interest at times, and the issue of international law enforcement at other times, it also used the same term to justify the application of the effects of some international treaties on states that are not party to it, or the application of United Nations decisions to non-member states. In addition to its employment of the same concept for the purpose of imposing its jurisdiction over some disputes that come out of its jurisdiction and expanding the scope of states that are bound by their decisions.